The Psychological Foundation of Logic in Sader Alden Alshirazi's Philosophy of Religion - Duaa khalil Ali, Hamdan Hasan Al-Onizat, Ayman Ghazi Alkhalaileh (Journal for ReAttach Therapy and Developmental Diversities, 2023)
The research subject offers an in-depth evaluation of the psychological foundation in light of Sader Alden Alshirazi’s philosophy of religion. Considering the interpretivism philosophy and case study design followed by an inductive research approach, the secondary collected data interpretation highlighted the basic conception of the psychological foundation and approached the contributional effort of Sader Alden Alshirazi in developing a psychological structure with a realistic significance. Simultaneously, the research indicated the philosophical interpretation regarding religion and its impacts on the mental states of human beings. The difference between traditional religious practices and transcendent practices has been explored in this study. The purpose of Sader Alden Alshirazi’s philosophy of religion refers to transcendent wisdom that prioritises the existence of God in the real version depicted. The correlation between psychological foundation and transcendent wisdom has been explained in this research to create a significance of the philosophy of religion metaphysically. On the other hand, the immutable approach of transcendent wisdom and its impacts on physical foundation has also been analysed in this research, adding a qualitative advantage to the research. The significance of the research justifiably reaches the goal of the study and evidentiary proves the actual contribution of Sader Alden Alshirazi’s philosophy of religion in psychological foundation in a logical manner.